Knowledge, Attitudes and Reported Practices of Dental Students in Omer-Almokhtar University Regarding Tobacco Effects on Oral Cavity Health (World Journal of Current Medical and Pharmaceutical Research, 2020)
Background: Tobacco use is risk factor causes of preventable death in the world. Oral health professions provide multiple opportunities for interventions throughout their careers that could lessen tobacco correlated diseases. Three factors knowledge, attitudes and behaviour are thought to play a starring role in determining the extent of tobacco use between patients and help dental clinicians to implement smoking cessation policy. Present study aimed to determine dental student's level of knowledge, awareness and practice regarding tobacco use and students/ dentists’ role in tobacco cessation.Subjects and methods; A total of 160 students were recruited from Faculty of Dentistry, Omer- Almokhter university, and surveyed using an anonymous self administered questionnaire. This questionnaire was based on intensive literature review. Cross-section study design was applied using a structured questionnaire which included data related to personal characteristics and assessment of KAP of participants.Results: one hundred eight students responded with (82.4%) were females and 17.6 % were males. That majority of responding students had high level of knowledge attainment on tobacco with the exception of knowledge about smokeless tobacco which was inadequate. Although, most students (92.6%) agreed that dentist has an important role in tobacco control and training regarding tobacco effects is sufficient to allow them to help their patients to quit smoking, only 56.6% give advices to their patients. The prevalence of smokers among students was low (4%).Recommendation Education about tobacco effects necessity involved in the curriculum from first year. Students should be given training about smoking cessation and counselling techniques and must be motivated to play their role in patients’ education regarding smoking.